Judge Priest - Ford, John, 1894-1973; Rogers, Will, 1879-1935; Fox Film Corporation; Cinetel Films ([Hollywood, CA] : Fox Film Corporation, 1934)
An episodic meditation on life and politics in a small Kentucky town still marked in 1890 by memories of the Civil War. Will Rogers loosely inhabits the role of Judge Priest who defies class and racial barriers and shames the community into an awareness of its intolerance. This portrayal of an imperfect but good rural communty is lent a certain depth by nostalgia for a lost pre-Civil War past. Populist sentiment prevails over the due processes of law.
Based on Irvin S. Cobb's character Judge Priest.
Will Rogers, Tom Brown, Anita Louise, Henry B. Walthall, David Landau, Stepin Fetchit.
Producer, Sol M. Wurtzel; photography, George Schneiderman; music, Cyril J. Mockridge.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 9, 2015)
Keywords: Comedy films; Feature films; Internet videos; Streaming video